Game change Obama and the Clintons, McCain and Palin, and the race of a lifetime - Heilemann, John. (New York Harper, 2010)
In Game Change, John Heilemann and Mark Halperin, two of the country's leading political reporters, use their unrivalved access to pull back the curtain on the Obama, Clinton, McCain, and Palin Campaigns. How did Obama convince himself that , despite the thinness of his resume, he could somehow beat the odds to become the nation's first African American president? How did the tumultuous relationship between the Clintons shape-and warp-Hillary's suspposedly unstoppable bid? What was behind her husband's furious outbursts and devastating political miscalculations? Why did McCain make novice novice governor of Alaska his running mate? and was Palin merely painfully out of her depth-or troubled in more serious ways?. Game Change answers those questions and more , laying bare secret history of the 2008 campaign
Includes index
Keywords: Obama, Barack, Clinton, Hillary Rodham. McCain, John Palin, Sarah Presidents of United States Election 2008. Political campaigns --United States